“What’s the Point of Having a Voice If You’re Gonna Be Silent?”: Youth Activism in Young Adult Literature - Connors, Sean P.; Trites, Roberta Seelinger (FRAME, Journal of Literary Studies, 2026)
A growing number of people are turning to young adult literature as a road map to address social injustice through activism, which suggests that literary texts are neither apolitical nor static works of art exploring ‘timeless’ themes. This article examines how two recent young adult protest novels, The Hate U Give by Angie Thomas (2017) and The Marrow Thieves by Claire Dimaline (2017), resist the emphasis that neoliberalism—an economic philosophy that advocates for free markets and deregulation—places on extreme individualism and competition. In doing so, these books model collective action as a remedy for neoliberal policies that perpetuate systemic oppression.